Mismatch negativity (MMN) amplitude as a biomarker of sensory memory deficit in amnestic mild cognitive impairment - Lindín, Mónica; Correa, Kenia; Zurrón, Montserrat; Díaz, Fernando (Frontiers in Aging Neuroscience, 2013)
It has been suggested that changes in some event-related potential (ERP) parameters associated with controlled processing of stimuli could be used as biomarkers of amnestic mild cognitive impairment (aMCI). However, data regarding the suitability of ERP components associated with automatic and involuntary processing of stimuli for this purpose are not conclusive. In the present study, we studied the Mismatch Negativity (MMN) component, a correlate of the automatic detection of changes in the acoustic environment, in healthy adults and adults with aMCI (age range: 50-87 years). An auditory-visual attention-distraction task, in two evaluations separated by an interval of between 18 and 24 months, was used. In both evaluations, the MMN amplitude was significantly smaller in the aMCI adults than in the control adults. In the first evaluation, such differences were observed for the subgroup of adults between 50 and 64 years of age, but not for the subgroup of 65 years and over. In the aMCI adults, the MMN amplitude was significantly smaller in the second evaluation than in the first evaluation, but no significant changes were observed in the control adult group. The MMN amplitude was found to be a sensitive and specific biomarker of aMCI, in both the first and second evaluation.